Unraveling Executive Functioning in Dual Diagnosis - Duijkers, Judith C. L. M.; Vissers, Constance Th. W. M.; Egger, Jos I. M. (Frontiers in Psychology, 2016)
In mental health, the term dual-diagnosis is used for the co-occurrence of Substance Use Disorder with another mental disorder. These co-occurring disorders can have a shared cause, and can cause/intensify each other's expression. Forming a threat to health and society, dual-diagnosis is associated with relapses in addiction-related behavior and a destructive lifestyle. This is due to a persistent failure to control impulses and the maintaining of inadequate self-regulatory behavior in daily life. Thus, several aspects of executive functioning like inhibitory, shifting and updating processes seem impaired in dual-diagnosis. Executive (dys-) function is currently even seen as a shared underlying key component of most mental disorders. However, the number of studies on diverse aspects of executive functioning in dual-diagnosis is limited. In the present review, a systematic overview of various aspects of executive functioning in dual-diagnosis is presented, striving for a prototypical profile of patients with dual-diagnosis. Looking at empirical results, inhibitory and shifting processes appear to be impaired for Substance Use Disorder combined with schizophrenia, bipolar disorder or cluster B personality disorders. Studies involving updating process tasks for dual-diagnosis were limited. More research that zooms in to the full diversity of these executive functions is needed in order to strengthen these findings. Detailed insight in the profile of strengths and weaknesses that underlies one's behavior and is related to diagnostic classifications, can lead to tailor-made assessment and indications for treatment, pointing out which aspects need attention and/or training in one's self-regulative abilities.